Hatshepsut’s Punt Reliefs: Their Structure and Function - Taterka, Filip.
The article examines the layout of Hatshepsut’s Punt reliefs, proposing a new interpretation of their internal structure and ideological function within the decorative programme of the Deir el-Bahari temple. The author argues that the reliefs form a cycle of subsequent scenes, starting at the southernmost end of the west wall, continuing through the south wall up to the northern part of the west wall. As for the scenes represented on the northernmost end of the west wall and on the north wall, it is argued that they should be viewed as forming a single ideological entity, which at the same time corresponds to the long historical inscription placed on the easternmost end of the south wall. That way the reliefs reflect both aspects of Egyptian eternity: the linear (in the cycle of subsequent episodes) and the circular one (in the ideological link between the southern- and northernmost extremities of the Punt Portico). As for the function of the reliefs, it is argued that they were supposed to magically repeat Hatshepsut’s Punt expedition and thus provide her divine father Amun-Ra with all exotic products necessary in his cult. The author also tries to demonstrate, how Hatshepsut was gradually identified with the goddess Hathor in her aspect of the Lady of Punt and the female counterpart of Amun-Ra throughout the Punt reliefs. http://dx.doi.org/10.5913/jarce.55.2019.a012